Pemetaan Penelitian Akad Mudharabah Pada Lembaga Keuangan Syariah: Studi Bibliometrik Vosviewer Dan Literature Review - Eka Wahyu Hestya Budianto (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
This study aims to determine the map of the development of research regarding Mudharabah contracts at Islamic Financial Institutions with a VOSviewer bibliometric study and literature review. The research was conducted over a period of 21 years from 2001 to 2021 by searching through the Garuda website (Digital Reference Garba) with the keyword Mudharabah/Mudharabah. And obtained 857 research articles. The search results were then analyzed descriptively, inputted, analyzed using VOSViewer and literature review to determine the visualization of topic developments and research around the Mudharabah contract. The results showed that the number of publications regarding Mudharabah contracts has increased significantly every year. Then, based on the results of research visualization using VOSviewer, the Mudharabah contract is divided into 8 clusters. Based on the results of the literature review, there are 8 main themes and 435 research topics regarding Mudharabah contracts at Islamic Financial Institutions.